2019
DOI: 10.21608/adjg.2019.5803.1024
|View full text |Cite
|
Sign up to set email alerts
|

The Remineralizing Effect of Incorporating Ca-Phosphate and Ca-Fluoride Nanoparticles into the Self-Etch Adhesives Used in Restoring Class I Cavities

Abstract: Purpose: This study was carried out to investigate the remineralizing effect of amorphous calcium phosphate (ACP) and calcium fluoride (CaF 2) nanoparticles incorporated in two-step self etch-adhesives (in vivo). Materials and Methods: The nanoparticles were incorporated into the bond of Clearfil TM SE Bond at a mass fraction of 10%. A total of ten patients in the age range of 17-30 years old, having at least 3 carious lower molars, were enrolled in this study (split mouth design). Class I cavity preparation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…15-b). This result was reported by another study which showed that slight matrix layer was observed in most samples when direct pulp capping by using BG after mechanical pulp exposures on rat molars at one week (28) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…15-b). This result was reported by another study which showed that slight matrix layer was observed in most samples when direct pulp capping by using BG after mechanical pulp exposures on rat molars at one week (28) .…”
Section: Discussionsupporting
confidence: 80%
“…Exposed pulps were directly capped with both tested materials. After pulp capping, resin composite restoration was used to provide immediate sealing as it has good sealing properties, due to recent improvements in adhesive bonding with cavity walls (11,28,29) . As there is a suggestion which states that the seal's provision opposing the entrance of bacteria could possibly be the highest crucial reason among a successful vital pulp therapy (20) .…”
Section: Discussionmentioning
confidence: 99%
“…This difference was not statistically significant (p=0.20). the cross-linking mechanism (2) . Cross-linking of dentin matrix collagen is a natural mechanism occurred in dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Although the resin monomers uniformly infiltrate the demineralized dentin and do not create a region of unprotected fibrils (2) ; but, small areas of incomplete monomer infiltration could be seen with the use of self-etching adhesives. Also, degradation of the hydrophilic resin monomers could be observed, leading to more collagen liable to hydrolysis (27) (28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation